Study on the Views of Nursing Students in the First Year and Fourth Year on Social Gender Equality - Nihat Şencan; Mehmet Z. Avcı (Galenos Publishing House, 2021)
Objective:This study was conducted to evaluate the perspective of nursing school students toward gender equality in Turkish Republic of Northern Cyprus.Method:The study was conducted as a descriptive and seeking relationship between variables research. The research sample consisted of first- and fourth-grade students enrolled in the nursing department of a foundation university in the fall/summer semester of the 2015-2016 academic year. A simple randomized sampling method was used in the study, and 124 students out of the study population of 175 were selected. Sociodemographic variables questionnaire and Gender Equality Scale were used as data collection tools.Results:The data were evaluated using mean, minimum and maximum values, percentage distribution, t-test, analysis of variance, post hoc Tukey test, and standard deviation tests. The mean score was 39.12 for traditional gender norms, 9.50 for social equality norms, and 48.62 for Gender Equality Scale. It was determined that the egalitarian gender norms of female students were statistically significant (p < .05) compared with the male students. In addition, it was determined that egalitarian gender norms in senior students were statistically significant (p < .05) compared with the first-year students.Conclucison:On the basis of the findings, the study makes some recommendations to encourage positive behavior and attitude in teenage students toward egalitarian gender roles. Participation of women in training programs, social activities, and courses about social gender equality or about other subjects in or outside the school should be supported.